Expeditious Synthesis of Novel β-Lactam-Substituted Polycyclic Fused Chromeno Pyrrole Derivatives from MBH Carbonates by Intramolecular [3+2]-Cycloaddition Reaction - Rajesh, Raju; Raghunathan, Raghavachary (Synlett, 2013)
A facile synthesis of tri- and tetracyclic fused chromeno pyrrole derivatives has been accomplished by intramolecular cycloaddition reaction of azomethine ylides generated from cyclic/acyclic secondary amino acids with O-allylated salicylaldehydes obtained from Morita–Baylis–Hillman carbonates of β-lactam aldehyde. The stereochemistry of the cycloadducts was confirmed on the basis of single crystal X-ray diffraction data.
Keywords: 1,3-dipolar cycloaddition; β-lactams; drug development; pyrroles